ChemInform Abstract: Nickel‐Catalyzed Cross‐Coupling of Redox‐Active Esters with Boronic Acids. Issue 50 (November 2016) - Wang, Jie; Qin, Tian; Chen, Tie‐Gen; Wimmer, Laurin; Edwards, Jacob T.; Cornella, Josep; Vokits, Benjamin; Shaw, Scott A.; Baran, Phil S.
Abstract: The reaction between N‐hydroxy‐tetrachlorophthalimide‐derived esters and boronic acids represents an alternative to well known Suzuki cross‐couplings.